2008
DOI: 10.2223/jped.1805
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxLDL autoantibodies and their correlation with lipid profile and nutritional status in adolescents

Abstract: ResumoObjetivo: Avaliar se o conteúdo de auto-anticorpos anti-LDL oxidada (anti-LDLox) no plasma de adolescentes correlaciona-se com suas medidas antropométricas e com o perfil lipídico.Métodos: O estudo incluiu 150 adolescentes com idade entre 10 e 15 anos, recrutados do ambulatório de obesidade da Universidade Federal de São Paulo (SP) e de escolas públicas de Piracicaba (SP). Foram avaliadas medidas antropométricas, como índice de massa corporal, circunferência de cintura e do braço, classificando os adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Overweight and obesity are associated with higher lipoprotein oxidation, both abdominal and general obesity were shown to be independently associated with circulating oxLDL, weight reduction may potentially reduce oxLDL,31 especially in patients with metabolic syndrome 32. Previous studies have suggested a correlation between anti-oxLDL autoantibodies and anthropometric variables, making anti-oxLDL concentration a potential biochemical indicator of risk of metabolic syndrome 33. Our results show a significant positive correlation between BMI and oxLDL antibodies.…”
Section: Discussionsupporting
confidence: 58%
“…Overweight and obesity are associated with higher lipoprotein oxidation, both abdominal and general obesity were shown to be independently associated with circulating oxLDL, weight reduction may potentially reduce oxLDL,31 especially in patients with metabolic syndrome 32. Previous studies have suggested a correlation between anti-oxLDL autoantibodies and anthropometric variables, making anti-oxLDL concentration a potential biochemical indicator of risk of metabolic syndrome 33. Our results show a significant positive correlation between BMI and oxLDL antibodies.…”
Section: Discussionsupporting
confidence: 58%
“…No correlation between antibodies and BMI was reported in children undergoing hemodialysis. 33 In contrast, Sanches et al 39 showed that overweight and obese adolescents had higher IgG antibody level than normoweight adolescents.…”
Section: Discussionmentioning
confidence: 93%